2014
DOI: 10.1128/aac.01449-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Melamino Nitroheterocycle as a Potential Lead for the Treatment of Human African Trypanosomiasis

Abstract: dThis paper reports an evaluation of a melamino nitroheterocycle, a potential lead for further development as an agent against human African trypanosomiasis (HAT). Studies on its efficacy, physicochemical and biopharmaceutical properties, and potential for toxicity are described. The compound previously had been shown to possess exceptional activity against Trypanosoma brucei in in vitro assays comparable to that of melarsoprol. Here, we demonstrate that the compound also was curative in the stringent acute mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…One way to facilitate the development of new drugs targeting HAT is to better understand the mechanism of action of existing treatments with the properties that underlie parasite selectivity incorporated into the development of new trypanocidal agents. For example, melamine rings have been incorporated into several compounds to exploit the substrate specificity displayed by the P2 adenosine transporter, a permease implicated in the uptake of pentamidine and melarsoprol (Stewart et al ., ; Baliani et al ., ; Chollet et al ., ; Klee et al ., ; Capes et al ., ; Giordani et al ., ). Similarly, a parasite nitroreductase (NTR), an enzyme responsible for the activation of nifurtimox (Wilkinson et al ., ; Hall et al ., ), has been used to screen nitroaromatic libraries for anti‐ T. brucei properties (Bot et al ., 2010; 2013; Hall et al ., 2010; 2012; Hu et al ., ; Papadopoulou et al ., 2011; 2012; 2013).…”
Section: Introductionmentioning
confidence: 97%
“…One way to facilitate the development of new drugs targeting HAT is to better understand the mechanism of action of existing treatments with the properties that underlie parasite selectivity incorporated into the development of new trypanocidal agents. For example, melamine rings have been incorporated into several compounds to exploit the substrate specificity displayed by the P2 adenosine transporter, a permease implicated in the uptake of pentamidine and melarsoprol (Stewart et al ., ; Baliani et al ., ; Chollet et al ., ; Klee et al ., ; Capes et al ., ; Giordani et al ., ). Similarly, a parasite nitroreductase (NTR), an enzyme responsible for the activation of nifurtimox (Wilkinson et al ., ; Hall et al ., ), has been used to screen nitroaromatic libraries for anti‐ T. brucei properties (Bot et al ., 2010; 2013; Hall et al ., 2010; 2012; Hu et al ., ; Papadopoulou et al ., 2011; 2012; 2013).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, when 20 mg/kg of this compound was administered daily by the intraperitoneal route for 4 consecutive days to mice infected with T. b. brucei , a curative effect was observed [ 187 , 188 ]. In another study [ 189 ], when the dose was increased to 40 mg/kg/day, mice infected with T. b. rhodesiense were also cured. These authors also observed that oral treatment with 100 mg/kg for 4 days gave rise to moderate activity, whereas 10 doses of 50 mg/kg given intraperitoneally did not provide cure in a stage 2 rodent model of infection.…”
Section: Development Of Nitroheterocyclic Drugs Against Trypanosomesmentioning
confidence: 99%
“…The genotoxicity observed in the Ames test is due to activation by bacterial type I NTR (similar to the enzymes found in trypanosomes)—a reaction that cannot be conducted by the mammalian type II NTR. Therefore, nitroheterocyclic compounds should be deeply examined, because they could be functional and non-genotoxic [ 189 , 191 , 204 ].…”
Section: Activation Of Nitroheterocyclic Compounds As a Key Factor In...mentioning
confidence: 99%